Peripheral ameloblastoma of the mandible: A case report. Issue 6 (November 2016) - Kaneko, Takahiro; Nakamura, Satoshi; Kawano, Ryutarou; Horie, Norio; Shimoyama, Tetsuo
Abstract: The extra-osseous/peripheral ameloblastoma (PA) is a relatively rare subtype of ameloblastoma, which develops in the soft tissues of the gingiva and oral mucosa. In this article, we describe a PA found in the gingiva of the right mandibular premolar region in a 70-year-old male. On oral examination, a firm, pedunculated mass with a granular surface and partial ulceration was found on the lingual gingiva of the right mandibular first premolar to the first molar. The pathological diagnosis of the incisional biopsy specimen was highly suspected to be PA with difficulty to differentiate from basal cell carcinoma (BCC). As the clinical history and features could not help to rule out the possibility of BCC, en bloc resection with safe margins was performed. Immunohistochemically, the tumor cells showed positivity for CK19 and p63 but Ber-EP4 was negative for tumor cells. The final histopathological diagnosis was peripheral ameloblastoma.